Mitochondrial DNA control region variation in Lebanon, Jordan, and Bahrain. (September 2019) - Zimmermann, Bettina; Sturk-Andreaggi, Kimberly; Huber, Nicole; Xavier, Catarina; Saunier, Jessica; Tahir, Mohammad; Chouery, Eliane; Jalkh, Nadine; Megarbane, Andre; Bodner, Martin; Coble, Michael; Irwin, Jodi; et al.
Highlights: We present mitochondrial DNA control region data in Middle Eastern populations that are scarce in the literature. A total of 610 individuals were typed from Lebanon (n = 195), Jordan (n = 202) and the Kingdom of Bahrain (n = 213). FST comparison revealed significant differences in mtDNA lineages between Bahrain and the two other populations. Haplogroup distributions confirm the FST observations. Abstract: This study investigated the mitochondrial DNA (mtDNA) control region variation in Middle Eastern populations (610 individuals from Lebanon, Jordan and the Kingdom of Bahrain) for which population data are scarce. FST comparison among populations revealed that there are significant differences in mtDNA distributions between Bahrain and the two other populations, while Lebanon and Jordan showed no significant differences. This was also reflected by the distribution of the observed lineages that differed prominently between Bahrain and the other two investigated populations. Jordan and Lebanon fit the hitherto known genetic results of the Levant population. Data are available via EMPOP (https://empop.online ) and GenBank.